Strategies of Islamic Religious Education Teachers in Preventing Deviant Behavior among Students at SMA Utama Medan - Vickry Pratama Ilyas; Mavianti Mavianti (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the strategies implemented by Islamic Religious Education (IRE) teachers in preventing deviant behavior among students at SMA Utama Medan. Deviant behavior among adolescents, such as violations of school rules, risky social interactions, and lack of discipline, has become a serious challenge in the educational context. Islamic Religious Education plays a strategic role in shaping students’ morality, religious attitudes, and social behavior. This research employed a qualitative approach using a descriptive method. Data were collected through classroom observations, in-depth interviews with IRE teachers, and documentation of learning activities and religious programs at the school. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that the strategies used by IRE teachers include value-based Islamic learning, teacher role modeling, habituation of religious activities, persuasive approaches and Islamic counseling, as well as collaboration with homeroom teachers and parents. These strategies contribute positively to the development of students’ religious character and to the prevention of deviant behavior at SMA Utama Medan.